Clinical concentration of sevoflurane had no short-term effect on the myelin sheath in prefrontal cortex of aged marmosets - Miao, Zhengjie; Jiang, Yi; Wang, Fangfang; Shi, Lingling; Zhou, Ren; Niu, Yixuan; Zhang, Lei (Frontiers in Neuroscience, 2024)
The fragile brain includes both the developing brain in childhood and the deteriorating brain in elderly. While the effects of general anesthesia on the myelin sheath of developing brain have been well-documented, limited research has explored its impact on degenerating brain in elderly individuals. In our study, aged marmosets in control group were only anesthetized with 6-8% sevoflurane and 100% oxygen (2 L/min) for 1-2 minutes for anesthesia induction. In addition to anesthesia induction, the anesthesia group was exposed to a clinical concentration of sevoflurane (1.5-2%) for 6 hours to maintain anesthesia. After anesthesia, scanning electron microscopy (SEM) and artificial intelligence-assisted image analysis were utilized to observe the effects of general anesthesia on the myelin sheath in prefrontal cortex (PFC) of aged marmosets. Compared with the control group, our findings revealed no evidence that 6 hours of sevoflurane general anesthesia altered the thickness of myelin sheath, the diameter of myelinated axons, and the g-ratio in prefrontal cortex of aged marmosets. Therefore, clinical concentration of sevoflurane may have no short-term effect on the myelin sheath in prefrontal cortex of aged marmosets.